Preschool children’s fast mapping of novel words in the presence of speech competitors - Grieco-Calub, Tina M.; Fang, Tiffany W.; Simeon, Katherine M. (The Journal of the Acoustical Society of America, 2017)
Children frequently learn new vocabulary in the presence of competing sounds. This study was designed to test the influence of speech competitors on children’s ability to learn novel label-object pairs. Preschool-aged children (N = 16) performed a fast-mapping task in both quiet (target speech = 60 dBSPL) and speech competitor conditions (58 dBSPL). In each condition, children were familiarized to three novel label-object pairs on a computer screen. Children were subsequently tested on whether they mapped each pair with a closed-set, three-alternative-forced-choice test: children pointed to the object that corresponded to the spoken label. On average, children learned equally well in each condition. Further inspection of individual data, however, showed a subset of children acquiring more label-object pairs in the competitor condition. The subject pool was split into two subgroups of children, those who performed > 5% better or worse in the competitor condition. Independent t-tests showed that children who performed better in the competitor condition had lower scores on an executive function test. Though counterintuitive, results suggest that children with poorer inhibitory control of irrelevant stimuli are better at fast mapping novel label-object pairs in the presence of acoustic competition. Cognitive demands associated with the fast-mapping task will be discussed.